2019
DOI: 10.1088/1755-1315/391/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and fruit quality characters of Pineapple (Ananas comosus L. Merr) cv. Queen on three sites planting: freshwater peat, brackish peat and alluvial soil

Abstract: The growth and fruit quality of the crop is strongly influenced by the environment in which it grows. The purpose of this study was to observe the growth and fruit quality of pineapple (Ananas comusus L. Merr) cv. Queen that cultivated in the three different ecosystems. Pineapple cv. Queen was planted in three different ecosystems, namely in freshwater peatlands, brackish water peatlands and Alluvial soils in Riau province. Morphology and fruit quality characters of pineapple were evaluated at each ecosystem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Regarding fruit length, the results obtained are close to the values reported in other studies [12,30]. In contrast, the diameter of fruits harvested in this study exceeds that reported for fruits of pineapple "Queen" cultivar, whose values were less than 10 cm [13].…”
Section: Physicochemical Characteristics Of the Fruitsupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding fruit length, the results obtained are close to the values reported in other studies [12,30]. In contrast, the diameter of fruits harvested in this study exceeds that reported for fruits of pineapple "Queen" cultivar, whose values were less than 10 cm [13].…”
Section: Physicochemical Characteristics Of the Fruitsupporting
confidence: 85%
“…Nevertheless, the technical level of agricultural practices can significantly influence the expression of the crop's genetic potential [7,12]. e records of the morphological characteristics of the pineapple plants reported in this study are lower than the values reached by "Queen" cultivar cultivated in three different ecosystems (freshwater peat, brackish peat, and alluvial soil), as they reached a height greater than 80 cm and D-leaf lengths over 65 cm [13]. e quantification of these morphological characteristics (including the number of leaves) is of great importance in pineapple cultivation because they are related to photosynthetic efficiency and fruit development [12][13][14].…”
Section: Plant Growth Parametersmentioning
confidence: 70%
“…TSSC ( 0 Brix) indicates the level of sweetness of the fruit, which is influenced by the TDA in fruit. Sweet taste is determined by TSSC/TDA; the higher the TSSC/TDA ratio, the sweeter the taste of the fruit (Rosmaina et al 2019). The highest edible part (%) was obtained from the Kuansing population, reaching 34%, which was not significantly different from the Gunung Sahilan population (32.60%) and Kuok population (32.18%), followed by the Kampar Kiri population (29.10%).…”
Section: Quantitative Characteristics Of Fruitmentioning
confidence: 99%
“…In addition, the accumulation of organic matter in peat soil can affect the sweetness level of the fruit. Characterization of other horticultural crops was reported by Rosmaina (2019) that pineapple plants grown on peat soil had higher fruit weight and pineapple fruit length than pineapples grown on mineral soils. This result might be due to the availability and uptake of nutrients in peat soils, which are higher than in mineral soils.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation